Method for preparing high-performance carbon microspheres based on grading of waste cotton textiles
By sorting waste cotton textiles by fluorescent probes and laser irradiation to determine their aging degree, and combining magnetron liquid crystal spinning and hydrothermal carbonization technologies, the problem of differences in the aging characteristics of waste cotton textiles has been solved, enabling the preparation of high-performance carbon microspheres and the efficient utilization of resources.
Patent Information
- Application Number
- CN202511205168.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-12-26
- Estimated Expiration
- 2045-08-27
AI Technical Summary
Existing technologies do not fully consider the differences in aging characteristics of waste cotton textiles in open-air environments, making it difficult to physically recycle high-aging materials. Furthermore, traditional methods for preparing carbon microspheres require high-purity raw materials or catalysts, which pollute the environment and have low utilization rates.
Fibers with different aging levels were sorted by fluorescent probe and laser irradiation. Lightly and moderately aged fibers were regenerated into high-strength fibers by magnetron liquid crystal spinning, while heavily aged fibers were directly hydrothermally carbonized and then activated with gradient KOH to expand pores to prepare carbon microspheres.
It enables precise utilization of fibers at different aging levels, improves the performance of regenerated fibers and the quality of carbon microspheres, reduces pollution, increases resource utilization and added value, and avoids the use of catalysts.
Smart Images

Figure CN120736525B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of making artificial filaments, and particularly relates to a method for preparing high-performance carbon microspheres based on waste cotton textiles. BACKGROUND
[0002] Cotton textiles, as materials mainly composed of natural cellulose, are widely used in clothing, home furnishing, medical treatment and other fields due to their excellent comfort, air permeability and moisture absorption. Among them, cellulose, as a renewable natural polymer, accounts for more than 90% of the composition of cotton textiles. However, during long-term use or storage, it will age due to factors such as heat, oxygen, ultraviolet light and mechanical wear, resulting in molecular chain breakage and reduced polymerization degree, and ultimately becoming waste cotton textiles. With the growth of global cotton consumption demand, the output of waste cotton textiles is increasing year by year. If they are treated by incineration or landfill, not only the cellulose resources will be wasted, but also toxic gases will be released or the soil and water sources will be polluted. Therefore, their resource utilization has become an important issue in the fields of environmental protection and resource recycling.
[0003] Carbon microspheres are a kind of carbonaceous materials with regular spherical structure. They have important application value in the fields of gas adsorption and environmental protection due to their surface rich in functional groups and adjustable pore structure. Using waste cotton textiles to prepare carbon microspheres can not only solve the problem of waste disposal, but also realize high-quality utilization of waste, which is a research hotspot in the field of waste resource utilization.
[0004] In the prior art, the recycling methods of waste cotton textiles mainly include physical regeneration (such as mechanical crushing and re-spinning), energy recovery (such as incineration for power generation), biodegradation (such as fermentation to produce fuel) and the like. However, physical regeneration is mostly suitable for low-aging-degree fibers, and high-aging-degree cotton fabrics are difficult to reuse due to the decline in mechanical properties; energy recovery has low utilization rate and pollutes the environment; biodegradation has a long cycle and the product has limited added value.
[0005] Therefore, it is necessary to improve the method for preparing high-performance carbon microspheres based on waste cotton textiles in the prior art to solve the above problems. SUMMARY
[0006] The present application overcomes the shortcomings of the prior art and provides a method for preparing high-performance carbon microspheres based on waste cotton textiles, aiming to solve the problem that the aging characteristics of waste cotton textiles in the prior art are not fully considered.
[0007] To achieve the above-mentioned purpose, the technical scheme adopted by the present application is as follows: a method for preparing high-performance carbon microspheres based on waste cotton textiles, comprising:
[0008] S1, pretreating the waste cotton textiles, and sorting the aging degree by fluorescence probe and laser irradiation to obtain severely aged hydrophobic fibers and lightly to moderately aged hydrophilic fibers; wherein the severe aging refers to fibers with a degree of polymerization of less than or equal to 500, and the light to moderate aging refers to fibers with a degree of polymerization between 500 and 1000;
[0009] S2, after the light to moderate aging hydrophilic fibers are treated by a repair system, a regenerated high-strength fiber is prepared by using a magnetron liquid crystal spinning;
[0010] S3, the severely aged hydrophobic fibers are prepared into carbon microspheres by hydrothermal carbonization combined with activation and hole expansion.
[0011] In a preferred embodiment of the present application, in step S1, the fluorescence probe is a carbonyl-sensitive fluorescence probe solution, the solute of which is 4-hydrazino-7-nitrobenzofurazan, the concentration of which is 0.01-0.05 mol / L, the solvent of which is an ethanol-water mixture with a volume ratio of 1:1-1.5, and the pH value of the solution is 5.0-6.0; the laser irradiation includes: first, using 600-620 nm laser irradiation for 10-20 seconds, the laser power density is 1-3 W / cm 2 , then using 510-530 nm laser irradiation for 5-15 seconds, the laser power density is 0.5-1.5 W / cm 2 ; the aging degree sorting is realized by horizontal airflow separation, the wind speed is 5-10 m / s, and the airflow channel length is 2-4 meters.
[0012] In a preferred embodiment of the present application, in step S1, the pretreatment includes mechanical opening and impurity removal and photocatalytic decontamination; the mechanical opening and impurity removal uses a four-roller opener, and the impurities are separated by a vibrating screen with a mesh size of 3-5 mm; the photocatalytic decontamination uses a TiO2 solution of anatase type, the TiO2 particle size is 20-50 nm, the solution concentration is 0.1-0.5 g / L, and the wavelength of the ultraviolet light irradiation is 240-260 nm for 30-60 minutes.
[0013] In a preferred embodiment of the present application, in step S2, the repair system is an ionic liquid repair system, which includes 1-butyl-3-methylimidazole chloride with a mass fraction of 80%-90% and glycidyl ether with a fiber mass of 5%-10%; the repair system treatment conditions are a temperature of 80-100℃, a stirring rate of 200-300 r / min, and a treatment time of 2-4 hours.
[0014] In a preferred embodiment of the present application, in step S2, the magnetic control liquid crystal spinning includes flowing the cellulose repair solution through a strong magnetic field channel with a magnetic field strength of 0.5-1.5T and a length of 1-2m, and a solution flow rate of 0.5-1.0m / min; then extruding into a coagulation bath for regeneration, the coagulation bath is a mixture of water and ethanol with a volume ratio of 3-4:1, the temperature is 20-30℃, and the winding rate is 50-100m / min.
[0015] In a preferred embodiment of the present application, in step S3, the hydrothermal carbonization is catalyst-free hydrothermal carbonization: the severely aged hydrophobic fibers in the first collector are mixed with water at a mass ratio of 1:10-1:20; and reacted at 200-250℃ and 1.5-3.0MPa for 4-8 hours.
[0016] In a preferred embodiment of the present application, in step S3, the activation and hole expansion includes mixing the carbon microsphere precursor with KOH at a mass ratio of 1:2-1:2.5, 1:2.5-1:3.5, or 1:3.5-1:4, and ball milling for 30-60 minutes at 300-400r / min by using a planetary ball mill; then calcining in stages, the first stage is at 200-400℃ under a nitrogen flow of 200-300mL / min for 50-70 minutes, the second stage is at 400-600℃ under a nitrogen flow of 400-500mL / min at a heating rate of 7-8℃ / min for 55-65 minutes, and the third stage is at 700-900℃ under a nitrogen flow of 300-400mL / min at a heating rate of 9-10℃ / min for 60-120 minutes.
[0017] In a preferred embodiment of the present application, in step S3, the carbon microspheres prepared after activation and hole expansion have a three-level continuous hierarchical pore structure, wherein the micropore diameter is 0.5-1.0nm, the proportion is 40%-50%; the mesopore diameter is 2-5nm, the proportion is 30%-40%; the macropore diameter is 50-200nm, the proportion is 15%-20%; and the graphitization degree of the carbon microspheres is 1.3-1.5.
[0018] In a preferred embodiment of the present application, in step S3, after activation and hole expansion, a purification and drying step is further included, the purification and drying includes soaking the crude product in a 1-2mol / L hydrochloric acid solution for 1-2 hours, washing with water until the pH is 6-7, and vacuum drying at 80-100℃ for 6-12 hours.
[0019] In a preferred embodiment of the present application, in step S3, the severely aged hydrophobic fibers do not need to be physically crushed before hydrothermal carbonization.
[0020] The present application solves the defects in the background art, and has the following beneficial effects:
[0021] (1) The application provides a method for preparing high-performance carbon microspheres based on waste cotton textiles, which proposes a grading recovery technical scheme for waste cotton textiles exposed to the open air. First, the waste cotton textiles are pretreated, and different aging degree fibers are separated by fluorescence probe and laser irradiation to obtain severely aged hydrophobic fibers and lightly to moderately aged hydrophilic fibers. The lightly to moderately aged fibers are repaired by ionic liquid and then used to produce regenerated high-strength fibers by magnetic control liquid crystal spinning; the severely aged fibers are directly prepared into carbon microspheres by hydrothermal carbonization combined with gradient KOH activation and hole expansion. This scheme realizes precise utilization of different aging fibers, improves the performance of regenerated fibers and the quality of carbon microspheres, reduces costs without catalysts, reduces pollution, and improves the resource utilization rate and added value of waste cotton textiles.
[0022] (2) The application is aimed at the characteristics of waste cotton textiles exposed to the open air, which have significant differences in aging degree. Fluorescence probe and laser irradiation are used to separate the aging degree: the carbonyl-sensitive fluorescence probe specifically binds to the carbonyl group generated by cellulose aging, and then different wavelength laser irradiation makes the severely aged fibers hydrophobic and the lightly to moderately aged fibers hydrophilic, and finally the two types of fibers are accurately distinguished by airflow separation; the fibers of different aging degrees can be treated directly, which avoids the problem of difficult utilization of highly aged fibers caused by mixed treatment; this separation method allows each type of fiber to match the most suitable recovery path, further improving the overall resource utilization rate of waste cotton textiles.
[0023] (3) For the lightly to moderately aged hydrophilic fibers, the application adopts an ionic liquid repair system combined with a magnetic control liquid crystal spinning process: the epoxy compounds in the ionic liquid can repair the broken molecular chains of the fibers, and the strong magnetic field can induce the directional arrangement of cellulose molecules, which can effectively restore the mechanical properties of the fibers to directly produce regenerated high-strength fibers; the physical regeneration in the prior art is only suitable for low-aged fibers, and it is difficult to restore the broken molecular chains, resulting in poor performance, while this process not only breaks through the performance limitations of lightly to moderately aged fibers, but also further expands the application scenarios of regenerated fibers in the high-strength field.
[0024] (4) For the severely aged hydrophobic fibers, the application directly uses hydrothermal carbonization and gradient KOH activation and hole expansion: taking advantage of the characteristics of broken molecular chains and low degree of polymerization, the hydrothermal carbonization can generate carbon microsphere precursors without catalysts, and then the gradient activation forms a hierarchical pore structure. The performance defects caused by aging in the traditional understanding are transformed into advantages for preparing carbon microspheres, and high-performance carbon microspheres are directly obtained; the existing technology for preparing carbon microspheres relies on high-purity raw materials or catalysts, and considers that aging will reduce the value of the material, while this process not only saves the use of catalysts, but also realizes the high-value utilization of severely aged fibers, further improving the functional performance of carbon microspheres such as adsorption. BRIEF DESCRIPTION OF DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the drawings needed in the embodiments or prior art description. Obviously, the drawings described below are only some embodiments of the present application, and for those skilled in the art, other drawings can also be obtained from these drawings without creative labor.
[0026] Figure 1 is a flow chart of the preferred embodiment of the present application;
[0027] Figure 2 is a whole process diagram of the preferred embodiment of the present application;
[0028] Figure 3 is a fluorescent probe sorting sub-flow chart of the preferred embodiment of the present application;
[0029] Figure 4 is a hierarchical pore construction diagram of the carbon microspheres of the preferred embodiment of the present application;
[0030] Figure 5 is a SEM diagram of the high-aging degree cotton fabric of the preferred embodiment of the present application, wherein (a) is the untreated cotton fabric; (b) is the cotton fabric after aging at 100°C; (c) is the cotton fabric after aging at 150°C; (d) is the cotton fabric after aging at 200°C; (e) is the cotton fabric after aging at 250°C;
[0031] Figure 6 is a SEM diagram of the carbon microspheres of the preferred embodiment of the present application, wherein (a) is the hydrothermal reaction for 2h; (b) is the hydrothermal reaction for 4h; (c) is the hydrothermal reaction for 6h;
[0032] Figure 7 is a multi-level pore structure of the carbon microspheres of the preferred embodiment of the present application. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only some embodiments of the present application, and not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the protection scope of the present application.
[0034] In the following description, many specific details are set forth in order to provide a thorough understanding of the present application, but the present application can also be implemented in other ways different from those described herein, therefore, the protection scope of the present application is not limited by the specific embodiments disclosed below.
[0035] SUMMARY
[0036] The application object of the present application is open-air piled waste cotton textiles. Such waste cotton textiles have experienced long-term sunlight irradiation, temperature changes, wind and rain erosion, and the fibers have significant aging degree differences. They are also mixed with impurities such as silt and oil stains.
[0037] The prior art does not fully consider the aging characteristic differences of waste cotton textiles in open-air environment when processing waste cotton textiles. A uniform processing method is used for cotton fabrics of different aging degrees, which leads to the fact that high-aging-degree materials are difficult to be physically regenerated and utilized due to the decline of mechanical properties.
[0038] The conventional idea believes that high-purity raw materials or catalysts need to be used to prepare carbon microspheres to promote carbonization reaction, and the aging of waste cotton textiles is a negative factor that reduces its utilization value. However, the present application breaks out of this cognition: through observation, it is found that open-air high-aging-degree cotton textiles are more prone to hydrolysis and polycondensation reaction in a high-temperature and high-pressure hydrothermal environment due to long-term aging, which causes the cellulose molecular chain to break, the degree of polymerization to decrease, and the hydrogen bond to weaken. This defect makes it easier for them to be converted into carbon microspheres without catalysts. In addition, the prior art has not considered the aging degree differences of waste cotton fibers. A uniform processing method is used for fibers of different aging states, which leads to the fact that the raw material reactivity is uneven, resulting in a disordered particle size distribution of carbon microspheres and poor performance stability.
[0039] Exemplary method:
[0040] As shown in Figure 1 , Figure 2 A method for preparing high-performance carbon microspheres based on waste cotton textiles, comprising the steps of:
[0041] S1, pretreating the waste cotton textiles, and sorting the aging degrees by means of fluorescence probes and laser irradiation to obtain severely aged hydrophobic fibers and mildly or moderately aged hydrophilic fibers;
[0042] S2, treating the mildly or moderately aged hydrophilic fibers with a repair system, and then spinning regenerated high-strength fibers by using a magnetic control liquid crystal;
[0043] S3, preparing carbon microspheres by hydrothermal carbonization combined with activation and hole expansion of the severely aged hydrophobic fibers.
[0044] In step S1, the open-air piled waste cotton textiles are mechanically opened and impurities are removed to obtain loose fibers;
[0045] The mechanical opening and impurity removal refers to a process of breaking the entangled state of the fibers of the waste cotton textiles by mechanical force and separating the physical impurities therefrom. In the present application, the open-air piled waste cotton textiles are put into an opener, the tearing action of the components such as the taker-in and beater in the opener is used to make the fiber bundles loose into single fibers or small fiber bundles, and then the silt, stones and other impurities are separated by a vibrating screen.
[0046] Open-air waste cotton textiles are piled up for a long time, which will form dense clumps due to extrusion and entanglement, and mixed with a large number of external impurities, including: 5-20mm diameter of sand particles, small stone blocks;
[0047] The opening process destroys the hydrogen bond and van der Waals force between fibers by mechanical force, so that the fiber bundle is disintegrated, providing uniform dispersed raw materials for subsequent decontamination and separation. The vibration screen separates by particle size difference, and the vibration screen aperture is set to 3-5mm. The reason is that the common physical impurities include: sand, stone diameter is more than 5mm, while the diameter of cotton fiber is only 10-20μm, and the length is 10-30mm, which can be retained through 3-5mm screen aperture, which not only ensures the impurity removal efficiency, but also avoids fiber loss.
[0048] The opening machine uses SBT600 four-roller opener, which is suitable for processing cloth head, cloth block, yarn head, knitted cloth block, etc. The waste cotton textiles can be put into the opener, and the tearing effect of the tines and beaters in the opener can make the fiber bundle loose into single fibers or small fiber bundles.
[0049] The opening machine removes macroscopic impurities efficiently by physical means, avoiding the wear of equipment such as reaction kettle and spinning channel in subsequent processing, and reducing the interference of impurities on the fiber regeneration or carbonization process. Among them, the metal ions in the sand can inhibit the formation of carbon microspheres.
[0050] In step S1, the loose fibers are immersed in a solution containing a photocatalyst, and the photocatalytic decontamination is carried out by ultraviolet light irradiation to remove organic pollutants on the surface of the fibers;
[0051] The photocatalytic decontamination refers to the process of using the strong oxidizing species generated by the photocatalyst under light to degrade organic pollutants. In this application, the photocatalyst is selected as anatase TiO2 solution, the particle size of TiO2 is 20-50nm, the solution concentration is 0.1-0.5g / L, the ultraviolet light wavelength is 240-260nm, and the irradiation time is 30-60 minutes; TiO2 has high chemical stability, no toxicity, and high response efficiency to ultraviolet light;
[0052] Under ultraviolet light irradiation, the valence band electrons of TiO2 are excited to the conduction band to form electron-hole pairs, the holes react with the adsorbed water molecules on the surface to generate hydroxyl radicals ( ), and the electrons react with oxygen to generate superoxide anion ( ). These active species can attack the C-C bond and C-O bond in organic pollutants such as oil (triglyceride) and bloodstains (hemoglobin), and oxidize and decompose them into CO2 and H2O.
[0053] Compared with traditional chemical decontamination, photocatalytic decontamination does not need to add harmful chemical reagents, has no secondary pollution, and can deeply degrade organic pollutants, while avoiding the molecular chain rupture of fibers caused by chemical corrosion.
[0054] As shown in Figure 3 Step S1, the decontaminated fiber is sprayed with a carbonyl-sensitive fluorescent probe solution, and after standing and permeation, it is irradiated with 600-620 nm laser and 510-530 nm laser respectively, so that the severely aged fiber is hydrophobized and the lightly or moderately aged fiber is hydrophilized, and then the severely aged hydrophobic fiber and the lightly or moderately aged hydrophilic fiber are obtained by air separation.
[0055] Specifically, the carbonyl-sensitive fluorescent probe solution refers to a functional solution that can specifically react with the carbonyl (C=O) produced by aging in the cellulose molecule, and realize the visual labeling of carbonyl content through the change of photo-physical or photo-chemical properties under certain conditions.
[0056] The specific composition of the solution is as follows: the solute is 4-hydrazino-7-nitrobenzofurazan (NBD-H), the concentration is 0.01-0.05 mol / L; the solvent is a mixture of ethanol and water with a volume ratio of 1:1-1.5; and the pH value of the solution is adjusted to 5.0-6.0 to promote the stability and reactivity of the probe molecule.
[0057] As shown in Figure 5 This is because during the aging of cellulose, the hydroxyl group (-OH) on the glucose unit is oxidized to carbonyl group (C=O) due to the effects of ultraviolet light oxidation, thermal oxidation and other effects, and the higher the aging degree, the higher the carbonyl content, wherein the carbonyl content of the severely aged fiber is 0.5-1.2 mmol / g, and the carbonyl content of the lightly or moderately aged fiber is 0.1-0.4 mmol / g.
[0058] The hydrazine group (-NH-NH2) in the NBD-H molecule can undergo nucleophilic addition-elimination reaction with the carbonyl group to form stable hydrazone compounds, and this reaction has high specificity and has no obvious effect on hydroxyl group, ether bond and other groups, ensuring that only the carbonyl sites produced by aging are labeled.
[0059] The labeled hydrazone compounds have strong absorption in the 600-620 nm red light band, while the unreacted NBD-H and a small amount of label on the lightly or moderately aged fiber have weak absorption in this band.
[0060] This absorption difference makes:
[0061] The severely aged fiber has high-efficiency light-heat conversion under 600-620 nm laser irradiation due to the large amount of label, and the local temperature rises to 80-120℃, realizing hydrophobization; high temperature leads to the movement of cellulose molecular segments on the surface of the fiber, and part of the hydroxyl groups are dehydrated to form ether bonds, while the surface energy is reduced, showing hydrophobicity;
[0062] Light and moderate aging fibers have less markers, low energy absorption under the same laser, and only mild heating to 40-60℃ under 510-530nm green light irradiation, maintaining hydrophilicity; only mild heating, promoting the adsorption of water molecules on the fiber surface to form hydrogen bonds, while the hydroxyl groups in the cellulose molecules remain active, showing hydrophilicity;
[0063] In the present application, the red light laser with a wavelength of 600-620nm is used to irradiate the fibers, and the laser power density is 1-3W / cm 2 , and the irradiation time is 10-20 seconds;
[0064] The green light laser with a wavelength of 510-530nm is used to irradiate the fibers, and in the present application, the laser power density is 0.5-1.5W / cm 2 , and the irradiation time is 5-15 seconds.
[0065] Then, the fibers are separated by horizontal airflow according to the difference in hydrophilicity and hydrophobicity, the wind speed is 5-10m / s, and the airflow channel length is 2-4m.
[0066] The severely aged hydrophobic fibers have small surface tension, weak adhesion to airflow, and short movement distance, falling into the first collector;
[0067] The light and moderate aging hydrophilic fibers have increased mass and strong adhesion to airflow due to the adsorption of water molecules, and have long movement distance, falling into the second collector.
[0068] Specifically, severe aging refers to fibers with a degree of polymerization of ≤500, and light and moderate aging refers to fibers with a degree of polymerization of 500-1000.
[0069] In step S1, the open and impurity-removed outdoor waste cotton textiles are subjected to photocatalytic decontamination, and then the hydrophilic and hydrophobic properties are differentiated by means of fluorescence probe and laser irradiation, and different aging degree fibers are separated by airflow, preparing for subsequent classification and regeneration treatment.
[0070] In step S2, the light and moderate aging hydrophilic fibers in the second collector are mixed with an ionic liquid repair system, heated and stirred for chain breaking repair and dissolution, to obtain a cellulose repair solution;
[0071] The ionic liquid repair system refers to a composite system using ionic liquid as solvent and adding epoxy compound as repair agent. In the present application, the ionic liquid is 1-butyl-3-methylimidazolium chloride ([BMIM]Cl) with a mass fraction of 80%-90%; the epoxy compound is glycidyl ether, and the addition amount is 5%-10% of the fiber mass; the heating temperature is 80-100℃, the stirring rate is 200-300r / min, and the treatment time is 2-4 hours.
[0072] The cellulose molecular chain of light and medium aged fiber has partial breakage, at this time, the degree of polymerization is reduced to 500-1000, while the original cotton has a degree of polymerization of about 1500-3000, and the exposed hydroxyl at the broken chain is easy to form intramolecular hydrogen bond, affecting the fiber performance. The ionic liquid [BMIM]Cl can gradually dissolve the fiber by destroying the hydrogen bond network between the cellulose molecules; the epoxy group of glycidyl ether is a three-membered ring structure, which occurs ring-opening reaction under heating conditions and grafts with the hydroxyl (-OH) at the broken chain of cellulose to form a -O-CH2-CH(OH)-CH2-O- connecting structure, resewing the broken molecular chain and restoring the degree of polymerization to 1200-1800.
[0073] Compared with the traditional alkali dissolution method, the ionic liquid has high selectivity for cellulose and does not dissolve impurities such as lignin and hemicellulose, and the repair process is carried out synchronously in the dissolution system, avoiding secondary pollution; the efficiency of the epoxy group grafting reaction is high, which can significantly restore the integrity of the cellulose molecular chain and provide high-quality raw materials for subsequent spinning.
[0074] In step S2, the cellulose repair solution flows through the strong magnetic field channel, the cellulose molecules are induced to arrange in orientation, and then are extruded into a coagulation bath for regeneration, wound into a fiber, and a regenerated high-strength fiber is obtained;
[0075] The strong magnetic field channel refers to a tubular channel capable of generating a uniform strong magnetic field, in the present application, the magnetic field strength is 0.5-1.5T, the channel length is 1-2 meters, and the solution flow rate is 0.5-1.0m / min; the coagulation bath is a mixture of water and ethanol with a volume ratio of 3-4:1, and the temperature is 20-30℃; the winding rate is 50-100m / min.
[0076] The cellulose molecular chain is in a random coil state in the ionic liquid, when flowing through the strong magnetic field, because the molecular chain has anisotropy, the magnetic susceptibility along the chain direction is higher than that perpendicular to the chain direction, and the molecular chain will arrange in orientation along the magnetic force line, and the orientation degree is ≥0.8 measured by X-ray diffraction.
[0077] When the random coil-like cellulose molecular chain flows through the strong magnetic field channel, it will be affected by the magnetic torque, the magnetic torque will drive the molecular chain to rotate, until =0 (along the magnetic force line direction), is the angle between the molecular chain and the magnetic force line, at this time, the torque is zero, and the thermodynamic stable state is reached. When the magnetic field strength is insufficient, the magnetic torque is too small to overcome the entanglement resistance between the molecular chains; when the strength is too high, the molecular chain will be excessively stretched, causing local breakage and reducing the fiber toughness.
[0078] The cellulose solution with oriented arrangement is extruded from the spinneret with a diameter of 0.1-0.2 mm into the coagulation bath, the ionic liquid rapidly diffuses to the coagulation bath, the cellulose molecules re-form a hydrogen bond network, and solidify into fibers, and the oriented arrangement of the molecular chains significantly improves the mechanical properties of the fibers.
[0079] The strong magnetic field channel device of the application selects a MagnetoAlign-2000 type magnetic control orientation channel, which is arranged in a Halbach array by a neodymium-iron-boron permanent magnet to form an axial uniform magnetic field, and the magnetic field strength can be adjusted by the distance between the permanent magnets.
[0080] The strong magnetic field channel body is made of non-magnetic austenitic stainless steel, with an inner diameter of 45-50 mm and a length of 1-2 meters, and the inner wall is polished to reduce the solution flow resistance; temperature sensors are arranged at both ends of the channel to avoid solution temperature fluctuations caused by magnetic field heating.
[0081] The cellulose solution with oriented arrangement is extruded from the spinneret and immediately enters the water-ethanol mixed coagulation bath;
[0082] The addition of ethanol reduces the solubility of the ionic liquid ([BMIM]Cl) in water, and accelerates the diffusion of the ionic liquid from the cellulose solution to the coagulation bath;
[0083] Water as a non-solvent enables the rapid formation of new hydrogen bond networks between cellulose molecular chains, solidifying into fibers; a volume ratio of 3:1 can balance the diffusion rate and solidification uniformity - if the water ratio is too high, it will cause rapid solidification on the surface to form a hard shell, and it will be difficult for the ionic liquid inside to diffuse, causing internal defects in the fiber; if the ethanol ratio is too high, the solidification will be too slow, and the molecular chains are prone to relaxation, resulting in a decrease in orientation degree.
[0084] Step S2 repairs the molecular chain defects of the lightly and moderately aged fibers through ionic liquid, and then induces molecular orientation arrangement and spinning through a strong magnetic field to obtain regenerated high-strength fibers, while the heavily aged hydrophobic fibers in the first collector enter step S3 to prepare carbon microspheres.
[0085] As shown in Figure 6 , in step S3, the heavily aged hydrophobic fibers in the first collector are directly mixed with water and placed in a high-temperature and high-pressure reaction kettle for catalyst-free hydrothermal carbonization to generate carbon microsphere precursors;
[0086] The catalyst-free hydrothermal carbonization refers to the process in which fiber fragments are converted into carbon microspheres through hydrolysis, polycondensation, etc. in a high-temperature and high-pressure water environment. In the application, the mass ratio of fiber fragments to water is 1:10-1:20, the reaction kettle temperature is 200-250℃, the pressure is 1.5-3.0 MPa, and the reaction time is 4-8 hours.
[0087] The severely aged hydrophobic fibers can be directly subjected to hydrothermal carbonization without physical crushing pretreatment such as steam explosion treatment. The self-aging characteristics and the previous sorting process of the severely aged hydrophobic fibers meet the requirements of the hydrothermal reaction. After long-term natural aging of the severely aged cotton textiles exposed to the open air, the cellulose molecular chains are significantly broken (polymerization degree ≤ 500), and the intermolecular hydrogen bond interaction is greatly weakened. The fiber bundle itself is in a loose state. At the same time, the laser irradiation (80-120°C) in step S1 further intensifies the movement of the molecular chains on the fiber surface, and part of the hydroxyl groups are dehydrated to form ether bonds, making the fiber structure more easily dispersed, and without the mechanical force of steam explosion, the fibers can be fully contacted with water. The high-pressure impact of steam explosion may cause irregular fracture of the already fragile aged fibers, which in turn destroys the balance of the length of the molecular chain fragments required for the formation of carbon microspheres.
[0088] The carbonyl (C=O) functional group introduced into the severely aged fibers acts as an electrophilic center, which can improve the reactivity of the cellulose molecules and promote their spontaneous hydrolysis under high temperature and high pressure conditions to generate small molecular sugars including glucose and fructose. These sugars further undergo polycondensation reactions under the assistance of carbonyl groups to form carbon microsphere precursors with a core-shell structure, and the particle size is generally between 500-1000 nm.
[0089] From the molecular mechanism, the presence of carbonyl groups effectively reduces the activation energy of the hydrolysis and polycondensation processes, allowing the reactions to proceed efficiently without the need for additional catalysts, thereby overcoming the dependence on noble metal catalysts in traditional carbon microsphere preparation processes.
[0090] Step S3 utilizes the carbonyl defects of the aged fibers to achieve self-catalytic reaction, reducing production costs while avoiding the impact of catalyst residues on the performance of carbon microspheres; the hydrothermal carbonization process is carried out in a closed system, with no toxic gas emissions, meeting the requirements of green technology.
[0091] As shown in Figure 4 , Figure 7 , in step S3, the carbon microsphere precursors are mixed with KOH at a gradient concentration ratio, and calcination activation is carried out under the synergistic action of staged temperature control and dynamic atmosphere, forming a three-stage continuous hierarchical pore structure.
[0092] Specifically, the carbon microsphere precursors obtained by hydrothermal carbonization have a particle size of 500-1000 nm, and the analytical pure KOH powder is mixed in a gradient ratio of 1:2-1:2.5, 1:2.5-1:3.5, and 1:3.5-1:4 by mass. The mixing process uses a planetary ball mill with a rotation speed of 300-400 r / min and a ball milling time of 30-60 minutes to ensure that the KOH particles have a particle size of 1-5 μm and are uniformly coated on the surface of the carbon microspheres.
[0093] First stage 200-400°C micropore seed layer construction:
[0094] The mixture with the ratio of 1:2-1:2.5 is placed in a tube furnace such as OTF-1200X, nitrogen is introduced, the flow rate is controlled at 200-300 mL / min, and the temperature is raised to 200-400℃ at a rate of 5℃ / min, and the temperature is kept at 200-300℃ for 30-40 minutes and at 300-400℃ for 20-30 minutes.
[0095] At this stage, KOH is slowly dissolved and weakly interacts with the carbonyl defect site C=O on the surface of the carbon microspheres, forming a temporary coordination bond -C-O-K through proton transfer. + This selective adsorption causes the etching reaction to occur only in the defect area, forming a micropore seed with a diameter of 0.5-1.0 nm and a pore density of 10 12 -10 13 cm 2 .
[0096] The second stage 400-600℃ interconnects the mesoporous network:
[0097] The mixture in the furnace is replaced with a system with a ratio of 1:2.5-1:3.5, the nitrogen flow is adjusted to 400-500 mL / min, the heating rate is increased to 7-8℃ / min, and the temperature is kept at 400-600℃, 400-500℃ for 30-35 minutes, and 500-600℃ for 25-30 minutes, and the temperature is kept for 1 hour.
[0098] As the temperature rises, K2O produced by the decomposition of KOH reacts with the active carbon at the edge of the micropore seed, causing the micropore to expand radially to 2-5 nm, while the pore walls of adjacent micropores fuse under the action of carbon migration, forming a mesoporous network with a diameter of 2-5 nm and a pore tortuosity of 1.2-1.5.
[0099] The third stage 700-900℃ macropore channel growth:
[0100] The mixture with a ratio of 1:3.5-1:4 is used, the nitrogen flow is maintained at 300-400 mL / min, the temperature is raised to 700-900℃ at a rate of 9-10℃ / min, and the temperature is kept at 700-800℃ for 30-60 minutes and at 800-900℃ for 30-60 minutes.
[0101] At high temperatures, high-concentration KOH produces K + with strong penetration, a diffusion coefficient of 10 -9 -10 -8 cm 2 / s, preferentially etching the intersection nodes of the mesoporous network, where the carbon density is lower than in other areas, forming macropores with a diameter of 50-200 nm. At the same time, the diffusion coefficient of carbon atoms at high temperatures increases to 10 -10 -10-9 cm 2 / s, so that the macropore wall forms a graphitized coating layer with a thickness of 5-10 nm. The macropore and the mesopore are connected through a funnel-shaped structure with a gradual change in pore size, and the transition zone has a length of 50-100 nm, ensuring the continuity of ion transmission.
[0102] After calcination, natural cooling to room temperature, the obtained crude product by acid washing, washing and vacuum drying.
[0103] Among them, the acid washing uses 1-2 mol / L hydrochloric acid solution, and the soaking time is 1-2 hours to remove the inorganic residues generated in the activation process; the water washing is to pH=6-7, the vacuum drying temperature is 80-100℃, and the drying time is 6-12 hours.
[0104] Step S3 sequentially performs catalyst-free hydrothermal carbonization, KOH activation and pore expansion, and purification and drying on the severely aged hydrophobic fibers to convert them into high specific surface area hierarchical porous carbon microspheres, realizing the conversion of aging defects to functional sites.
[0105] Example 1:
[0106] Mechanical opening and impurity removal: The waste cotton textiles exposed to the open air are put into an SBT600 four-roller opener, and the fibers are torn into single fibers and small fiber bundles by the action of the tines and beaters. Then, the mud, sand and stones with a diameter of 5-20 mm are separated through a 4mm aperture vibrating screen, and loose fibers are obtained.
[0107] Photocatalytic decontamination: the loose fibers are immersed in a solution containing anatase TiO2, wherein the particle size of TiO2 is 30 nm and the concentration of the solution is 0.3 g / L; 250 nm ultraviolet light is used for irradiation for 45 minutes, and the stirring rate of the solution is maintained at 80 r / min during the irradiation.
[0108] Fluorescent probe labeling and laser sorting:
[0109] The decontaminated fibers are sprayed with a carbonyl-sensitive fluorescent probe solution, the solute of which is 4-hydrazino-7-nitrobenzofurazan (NBD-H) with a concentration of 0.03 mol / L, and the solvent is an ethanol-water mixture (volume ratio 1:1.2), and the pH of the solution is adjusted to 5.5; and the penetration is allowed to stand for 20 minutes.
[0110] 610 nm red light laser is used for irradiation with a laser power density of 2 W / cm² and an irradiation time of 15 seconds; then 520 nm green light laser is used for irradiation with a laser power density of 1 W / cm² and an irradiation time of 10 seconds. 2
[0111] The severely aged hydrophobic fibers in the first collector and the lightly to moderately aged hydrophilic fibers in the second collector are collected by horizontal airflow separation with an airflow speed of 7 m / s and an airflow channel length of 3 meters.
[0112] Ionic liquid repair and dissolution, the second collector in the light and moderate aging hydrophilic fiber with ionic liquid repair system mixed, where the ionic liquid is 1-butyl-3-methyl imidazole chloride ([BMIM]Cl), mass fraction of 85%; epoxy compound is glycidyl ether, the amount of 7% of the fiber mass; stirring at 90 ℃ for 3 hours at 250 r / min, get cellulose repair solution.
[0113] Magnetic control liquid crystal spinning:
[0114] The cellulose repair solution flows through the strong magnetic field channel, the magnetic field strength is 1.0T, the channel length is 1.5 meters, and the solution flow rate is 0.7m / min.
[0115] Extruded from 0.15mm aperture spinneret, into the coagulation bath (water and ethanol volume ratio 3.5:1, temperature 25℃), at a speed of 75m / min into a fiber, get regenerated high strength fiber.
[0116] Hydrothermal carbonization: the first collector in the heavy aging hydrophobic fiber with water mixed with mass ratio of 1:15, placed in high temperature and high pressure reactor, under the condition of 220℃, 2.0MPa for 6 hours, carbon microsphere precursor is generated.
[0117] Gradient concentration KOH activation and hole expansion:
[0118] The carbon microsphere precursor and KOH are mixed with gradient mass ratio of 1:2.2, 1:3 and 1:3.8 respectively, and the planetary ball mill (speed 350r / min) is used for ball milling for 45 minutes.
[0119] Staged calcination:
[0120] The first stage (200-400℃): nitrogen flow 250mL / min, 200-300℃ for 35 minutes, 300-400℃ for 25 minutes;
[0121] The second stage (400-600℃): nitrogen flow 450mL / min, heating rate 7.5℃ / min, 400-500℃ for 33 minutes, 500-600℃ for 27 minutes;
[0122] The third stage (700-900℃): nitrogen flow 350mL / min, heating rate 9.5℃ / min, 700-800℃ for 45 minutes, 800-900℃ for 45 minutes.
[0123] S340, purification and drying: the crude product after calcination is soaked in 1.5mol / L hydrochloric acid solution for 1.5 hours, and then washed with water to pH=6.5; vacuum drying at 90℃ for 9 hours, get hierarchical porous carbon microspheres.
[0124] Example 2:
[0125] A method for preparing high-performance carbon microspheres based on waste cotton textiles, the same as in Example 1, and the difference is that the concentration of NBD-H is 0.01 mol / L.
[0126] Example 3:
[0127] A method for preparing high-performance carbon microspheres based on waste cotton textiles, the same as in Example 1, and the difference is that the concentration of NBD-H is 0.02 mol / L.
[0128] Example 4:
[0129] A method for preparing high-performance carbon microspheres based on waste cotton textiles, the same as in Example 1, and the difference is that the concentration of NBD-H is 0.04 mol / L.
[0130] Example 5:
[0131] A method for preparing high-performance carbon microspheres based on waste cotton textiles, the same as in Example 1, and the difference is that the concentration of NBD-H is 0.05 mol / L.
[0132] Example 6:
[0133] A method for preparing high-performance carbon microspheres based on waste cotton textiles, the same as in Example 1, and the difference is that the magnetic field strength is 0.5T.
[0134] Example 7:
[0135] A method for preparing high-performance carbon microspheres based on waste cotton textiles, the same as in Example 1, and the difference is that the magnetic field strength is 1.5T.
[0136] Example 8:
[0137] A method for preparing high-performance carbon microspheres based on waste cotton textiles, the same as in Example 1, and the difference is that the carbon microsphere precursor and KOH are in a gradient mass ratio of 1:2, 1:2.8, 1:3.5.
[0138] Example 9:
[0139] A method for preparing high-performance carbon microspheres based on waste cotton textiles, the same as in Example 1, and the difference is that the carbon microsphere precursor and KOH are in a gradient mass ratio of 1:2.1, 1:3.2, 1:3.7.
[0140] Example 10
[0141] A method for preparing high-performance carbon microspheres based on waste cotton textiles, the same as in Example 1, and the difference is that the carbon microsphere precursor is mixed with KOH at a gradient mass ratio of 1:2.3, 1:2.9, and 1:3.9.
[0142] Comparative Example 1
[0143] A method for preparing high-performance carbon microspheres based on waste cotton textiles, the same as in Example 1, and the difference is that the fluorescent probe labeling and laser sorting steps are not performed, and the decontaminated fibers are directly mixed and processed. Part of the fibers is processed according to the ionic liquid repair and magnetic control liquid crystal spinning process of Example 1, and the other part is directly processed by hydrothermal treatment for carbon microsphere preparation process. The fibers are not distinguished between light, moderate, and severe aging.
[0144] Comparative Example 2
[0145] A method for preparing high-performance carbon microspheres based on waste cotton textiles, the same as in Example 1, and the difference is that in the ionic liquid repair and dissolution step, no epoxy compound (glycidyl ether) is added, only 85% by mass of 1-butyl-3-methylimidazolium chloride ([BMIM]Cl) is used at 90°C with stirring at 250 r / min for 3 hours, and the remaining step parameters are consistent with Example 1.
[0146] Experimental Example 1
[0147] In this experimental example, Example 1, Example 2, Example 3, Example 4, Example 5, Comparative Example 1, and the influence of fluorescent probe concentration (NBD-H concentration) on fiber sorting effect are analyzed.
[0148] Analysis method: The fluorescence intensity of the fiber surface after sorting is measured by fluorescence spectrophotometer, and the labeling rate of the fiber surface carbonyl (C=O) is detected by X-ray photoelectron spectroscopy (XPS); the actual aging degree (carbonyl content) of the fibers in the first and second collectors is counted, and the sorting accuracy (the proportion of fibers with target aging degree in the total fibers collected) is calculated.
[0149] Analysis characteristics: correlation between fluorescent probe concentration and carbonyl labeling rate, sorting accuracy, and difference in hydrophilic and hydrophobic properties of fiber surface;
[0150] Table 1 Influence of fluorescent probe concentration on fiber sorting effect
[0151]
[0152] In Experimental Example 1, the influence of the concentration of the fluorescent probe on the sorting effect is due to the specific reaction mechanism of NBD-H with carbonyl. The carbonyl content generated by the aging of cellulose increases with the degree of aging, and the hydrazine group of NBD-H will undergo nucleophilic addition reaction to form stable hydrazone compounds. When the concentration is 0.01 mol / L, the number of probe molecules is insufficient to cover the high content of carbonyl on the surface of severely aged fibers, resulting in low fluorescence labeling rate, and the difference between hydrophilic and hydrophobic is not significant after laser irradiation, so the sorting accuracy decreases. When the concentration is increased to 0.03 mol / L, the probe and carbonyl reach saturation, the surface of the severely aged fiber is densely labeled with the probe, and after red light irradiation, the photo-thermal conversion efficiency is the highest, the surface hydroxyl group is dehydrated to form ether bond, and the hydrophobic contact angle increases significantly; while the lightly and moderately aged fibers have less labeling, and the green light irradiation only mildly heats to keep hydrophilic, the difference between hydrophilic and hydrophobic reaches the maximum, and the sorting accuracy is the highest. When the concentration exceeds 0.03 mol / L, the excess probe is prone to non-specific accumulation on the surface of the fiber, which interferes with the uniformity of photo-thermal conversion, resulting in a slight decrease in sorting accuracy. Comparative Example 1 cannot distinguish the carbonyl content by fluorescence labeling and laser irradiation, so it cannot realize sorting by utilizing the laser-induced hydrophilic and hydrophobic difference, and can only randomly distribute the fibers, resulting in a significant decrease in accuracy, which directly verifies the key role of specific labeling and photo-thermal differentiation in the grading recovery.
[0153] Experimental Example 2
[0154] In this experimental example, the influence of magnetic field strength on the performance of regenerated high-strength fibers was analyzed by selecting Example 1, Example 6, Example 7, and Comparative Example 2.
[0155] Analysis method: X-ray diffractometer was used to measure the molecular orientation degree of the fiber; electronic single fiber strength tester was used to test the breaking strength and breaking elongation of the fiber; scanning electron microscope (SEM) was used to observe the surface morphology and cross-sectional structure of the fiber.
[0156] Analysis characteristics: relationship between magnetic field strength and molecular orientation degree, mechanical properties of fiber (breaking strength, breaking elongation), and integrity of fiber microstructure.
[0157] Table 2 Influence of magnetic field strength and repair agent on the performance of regenerated high-strength fibers
[0158]
[0159] In Experimental Example 2, the influence of magnetic field strength and the repairing agent on the performance of regenerated fibers is essentially the synergistic effect of molecular orientation and molecular chain integrity. Cellulose molecular chains have anisotropy and will be arranged along the magnetic force lines under the action of magnetic torque in a magnetic field. When the magnetic field strength is 0.5 T, the magnetic torque is insufficient to overcome the entanglement resistance between molecular chains, the molecular orientation degree is low, and the stress is not uniformly dispersed when the fiber is stressed, so the breaking strength is low. When the magnetic field strength is 1.0 T, the magnetic torque and the molecular chain movement reach a balance, the orientation degree is significantly improved, and the ring-opening reaction of the epoxy compound ternary ring structure occurs under heating, and the grafting reaction with the hydroxyl group at the cellulose chain breakage site occurs to form a stable connection structure, repair the broken molecular chains, and the synergistic effect of the two makes the fiber breaking strength reach the highest. When the magnetic field strength is 1.5 T, the over-high magnetic field causes the molecular chains to be stretched too much, and part of the chain segments are broken due to excessive stress. Although the orientation degree slightly increases, the overall mechanical properties slightly decrease. Comparative Example 2 cannot repair the molecular chain breakage of the slightly and moderately aged fibers due to the absence of epoxy compound, and even if the molecular orientation degree induced by the magnetic field reaches a certain level, the broken molecular chains will still become weak points under stress, resulting in a significant decrease in fiber strength. This shows that the repair of molecular chain integrity is a prerequisite for the improvement of mechanical properties.
[0160] Experimental Example 3:
[0161] In this experimental example, the influence of the gradient mass ratio of the carbon microsphere precursor to KOH on the structure of the carbon microspheres was analyzed by selecting Example 1, Example 8, Example 9, Example 10, and Comparative Example 1.
[0162] Analysis method: The specific surface area, total pore volume, and pore size distribution of the carbon microspheres were determined by nitrogen adsorption-desorption instrument; the microstructure and hierarchical pore structure of the carbon microspheres were observed by transmission electron microscopy (TEM); and the graphitization degree of the carbon microspheres was analyzed by X-ray diffraction.
[0163] Analysis characteristics: Hierarchical pore structure parameters (proportion of micropores / mesopores / macropores), graphitization degree of carbon microspheres.
[0164] In experimental example 3, the influence of the mass ratio of KOH gradient and the raw material grading treatment on the structure of carbon microspheres is due to the matching mechanism of step-by-step etching and the characteristics of the raw material. KOH has different effects at different stages: at low proportions, KOH slowly dissolves and reacts with the carbonyl defect sites on the surface of the carbon microspheres, forming micropore seeds; at medium proportions, the active species produced by KOH decomposition promote the expansion and fusion of the micropores into a mesoporous network; at high proportions, the active species preferentially etch the mesoporous intersection nodes, forming macropores. The gradient proportion of example 1 matches the three-step etching requirements, making the proportions of micropores, mesopores, and macropores balanced. A low proportion will result in insufficient mesopore generation, and a high proportion will result in excessive etching of micropores. Comparative example 1 is not graded, and the light and moderate aging fibers in the raw material have high degrees of polymerization and dense structures, making it difficult for KOH to uniformly etch them, resulting in a disorderly pore structure with a high proportion of macropores. At the same time, the ungraded fibers have many impurities, which interfere with the ordered arrangement of carbon atoms, reducing the degree of graphitization. This result confirms that severely aged fibers are more likely to form an ordered hierarchical pore structure through step-by-step etching due to molecular chain breakage and loose structure, and that raw material grading is the basis for achieving this effect.
[0165] The above is based on the ideal embodiment of the present application, and through the above description, relevant personnel can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the contents of the specification, and must be determined by the scope of the claims.
Claims
1. A method for preparing high-performance carbon microspheres based on grading of waste cotton textiles, characterized in that, The method comprises the steps of: S1, pretreating the waste cotton textiles, and sorting the aging degree by means of fluorescence probe and laser irradiation to obtain severely aged hydrophobic fibers and lightly to moderately aged hydrophilic fibers; wherein the severe aging refers to fibers with a degree of polymerization of less than or equal to 500, and the light to moderate aging refers to fibers with a degree of polymerization of between 500 and 1000; In step S1, the fluorescent probe is a carbonyl-sensitive fluorescent probe solution, the solute of which is 4-hydrazino-7-nitrobenzofurazan, the concentration of which is 0.01-0.05 mol / L, the solvent of which is an ethanol-water mixture with a volume ratio of 1:1-1.5, and the pH value of the solution is 5.0-6.0; the laser irradiation comprises: first, using 600-620 nm laser irradiation for 10-20 seconds, the laser power density is 1-3 W / cm 2 , and then using 510-530 nm laser irradiation for 5-15 seconds, the laser power density is 0.5-1.5 W / cm 2 ; the aging degree sorting is achieved by horizontal airflow separation, the wind speed is 5-10 m / s, and the airflow channel length is 2-4 meters. S2, after the light to moderate aging hydrophilic fibers are treated by a repair system, the regenerated high-strength fibers are prepared by means of magnetic control liquid crystal spinning; the repair system is an ionic liquid repair system, which comprises 80-90% by mass fraction of 1-butyl-3-methylimidazolium chloride and 5-10% by mass of glycidyl ether; In step S2, the magnetic control liquid crystal spinning comprises flowing the cellulose repair solution through a strong magnetic field channel with a magnetic field strength of 0.5-1.5T and a length of 1-2m at a solution flow rate of 0.5-1.0m / min; then extruding into a coagulation bath for regeneration, the coagulation bath is a mixture of water and ethanol with a volume ratio of 3-4:1, the temperature is 20-30℃, and the winding rate is 50-100m / min; S3, the severely aged hydrophobic fibers are prepared into carbon microspheres by means of hydrothermal carbonization combined with activation and hole expansion.
2. The method for preparing high-performance carbon microspheres based on waste cotton textiles according to claim 1, characterized in that: In step S1, the pretreatment comprises mechanical opening and light catalysis; the mechanical opening adopts a four-roller opener, and the impurities are separated by a vibrating screen with a pore size of 3-5mm; the light catalysis adopts a TiO2 solution with anatase TiO2 and a particle size of 20-50nm, and the solution concentration is 0.1-0.5g / L, and the solution is irradiated by ultraviolet light with a wavelength of 240-260nm for 30-60 minutes.
3. The method for preparing high-performance carbon microspheres based on waste cotton textiles according to claim 1, characterized in that: In step S2, the repair system treatment conditions are a temperature of 80-100℃, a stirring rate of 200-300r / min, and a treatment time of 2-4 hours.
4. The method for preparing high-performance carbon microspheres based on waste cotton textiles according to claim 1, characterized in that: In step S3, the hydrothermal carbonization is catalyst-free hydrothermal carbonization: the severely aged hydrophobic fibers in the first collector are mixed with water at a mass ratio of 1:10-1:20; the mixture is reacted at 200-250℃ and 1.5-3.0MPa for 4-8 hours.
5. The method for preparing high-performance carbon microspheres based on waste cotton textiles according to claim 1, characterized in that: In step S3, the activation and hole expansion comprise mixing the carbon microsphere precursor with KOH at a mass ratio of 1:2-1:2.5, 1:2.5-1:3.5, or 1:3.5-1:4, ball milling the mixture by means of a planetary ball mill at 300-400r / min for 30-60 minutes, then calcining the mixture in stages, the first stage is at 200-400℃, the nitrogen flow rate is 200-300mL / min, and the mixture is kept at the temperature for 50-70 minutes, the second stage is at 400-600℃, the nitrogen flow rate is 400-500mL / min, the temperature rising rate is 7-8℃ / min, and the mixture is kept at the temperature for 55-65 minutes, and the third stage is at 700-900℃, the nitrogen flow rate is 300-400mL / min, the temperature rising rate is 9-10℃ / min, and the mixture is kept at the temperature for 60-120 minutes.
6. The method for preparing high-performance carbon microspheres based on waste cotton textiles according to claim 1, characterized in that: In step S3, the activated and re-holed carbon microspheres have a three-level continuous hierarchical pore structure, wherein the micropore diameter is 0.5-1.0 nm, the proportion is 40-50%; the mesopore diameter is 2-5 nm, the proportion is 30-40%; the macropore diameter is 50-200 nm, the proportion is 15-20%; and the graphitization degree of the carbon microspheres is 1.3-1.
5.
7. The method for preparing high-performance carbon microspheres from waste cotton textiles according to claim 1, characterized in that: In step S3, the activated and re-holed carbon microspheres further include a purification and drying step, wherein the purification and drying is that the crude product is soaked in a 1-2 mol / L hydrochloric acid solution for 1-2 hours, washed with water until the pH is 6-7, and then dried at 80-100 DEG C under vacuum for 6-12 hours.
8. The method for preparing high-performance carbon microspheres based on waste cotton textiles according to claim 1, characterized in that: In step S3, the heavily aged hydrophobic fibers do not need to be physically crushed and pretreated before being subjected to hydrothermal carbonization.
Citation Information
Patent Citations
Organism-associated substance microarray and detecting method using it
JP2001228148A
KR1018026720000B1